(untitled) (Asian Journal of Social Science Studies, 2025)
The well-being determinants of two groups of older adults by employment status in Abu Dhabi were examined using data from the fourth cycle of the Abu Dhabi Quality-of-Life Survey. The first group are those who are employed, while the second group includes those who are retired, non-working, or unemployed. Using descriptive statistics, ANOVA, and regression, this research shows that working older adults recorded significantly more positive well-being outcomes than non-working older adults. Data suggests that the most significant well-being factors favoring working older people are pertaining to income change, income satisfaction, ability to make ends meet, subjective health, mental health, participating in volunteer activities, and social trust. The non-working older people score more positive outcomes on a few indicators, including frequency of meeting with friends, quality time spent with family, and satisfaction with family life. Further analysis reveal that female older adults record more negative well-being indicators than males, regardless of whether they work or not. The findings are discussed in the context of Abu Dhabi, as well as in light of international literature. Policy directions, limitations and future research are also discussed.